2014
DOI: 10.1007/s00417-014-2622-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of 3T MRI in assessment of optic nerve volume in glaucoma

Abstract: MRI measured optic nerve volume is a reliable method of assessing glaucomatous damage beyond the optic nerve head. A value of 236 mm(3) and below can be used to define severe glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…[ 44 ] Using a different MRI protocol, Ramli et al observed a significantly lower ION volume in advanced glaucoma compared to mild glaucoma or control groups, but no difference was found between mild glaucoma and control groups. [ 21 ] Our results are, at least in part, consistent with those studies, since the advanced glaucoma group had smaller ION diameter and cross-sectional area than the control group in all studied distances from the eye. This difference was also observed when the advanced glaucoma group was compared with the mild glaucoma group, except for the ION cross-sectional area at 5 mm from the eye.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…[ 44 ] Using a different MRI protocol, Ramli et al observed a significantly lower ION volume in advanced glaucoma compared to mild glaucoma or control groups, but no difference was found between mild glaucoma and control groups. [ 21 ] Our results are, at least in part, consistent with those studies, since the advanced glaucoma group had smaller ION diameter and cross-sectional area than the control group in all studied distances from the eye. This difference was also observed when the advanced glaucoma group was compared with the mild glaucoma group, except for the ION cross-sectional area at 5 mm from the eye.…”
Section: Discussionsupporting
confidence: 92%
“…[ 14 , 43 ] Using this method, we found smaller ION dimensions at different distances from the eye in glaucomatous relative to normal ones, which is consistent with previous MRI studies. [ 15 , 21 , 44 ] In one such MRI study, Chen et al described a smaller cross-sectional area of the ION in patients with advanced glaucoma compared to an age- and sex-matched control group. [ 44 ] Using a different MRI protocol, Ramli et al observed a significantly lower ION volume in advanced glaucoma compared to mild glaucoma or control groups, but no difference was found between mild glaucoma and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ramli and collegues 17 used 3 Tesla magnetic resonance imaging (MRI) to evaluate optic nerve head volume and found significantly lower nerve volume in both eyes of patients with severe and mild glaucoma groups compared to controls. Optic nerve volume less than 236 mm(3) was 96 % sensitive and 80% specific for severe glaucoma by visual field criteria.…”
Section: Introductionmentioning
confidence: 99%